A Theory of Marketing Outline of a Social Systems Perspective - Lüdicke, Marius; SpringerLink (Online service) (Wiesbaden : Deutscher Universitätsverlag : Imprint: Deutscher Universitätsverlag, 2006)
Marketing has become one of the most influential forces in contemporary market economies. Yet despite ubiquitous empirical presence, uncountable textbook definitions, and sixty years of scholarly work, a coherent sociological understanding of this powerful concept is still amiss. Drawing on Luhmannian social systems theory, historical analysis, and four qualitative studies, the author theorizes on the marketing function as a self-contained system of communications. It is argued that marketing systems prosper within a host organization if and as long as they successfully influence observers' preferences towards particular brands. On these conceptual foundations a comprehensive brand- and communication-centered theory is developed that fulfills Alderson', Cox' and Bartels' foundational requirements for a general theory of marketing in an unprecedented way.
Theory -- Critique -- Methods -- Marketing as a Social System -- Discussion -- Conclusions.
Keywords: Marketing; Marketing